Therapiesteuerung der COPD durch eosinophile Granulozyten? - Magnussen, Helgo (DMW - Deutsche Medizinische Wochenschrift, 2019)
Symptomatic patients with COPD reporting about repeated exacerbations in their history (group D according to GOLD recommendations) are treated with dual bronchodilation (LAMA/LABA) with potential benefits from additional ICS. Eosinophils in peripheral blood are considered as potential biomarkers to predict exacerbations. > 300 cells/µL or 4 % of eosinophils in peripheral blood are recommended to treat the patients with additional ICS. In clinical practice, about 10 – 15 % of patients with COPD are classified as group D according to GOLD. < 20 % have increased eosinophils in peripheral blood. Thus, ICS therapy should be restricted to a minority of patients with COPD
Keywords: COPD; inhalative Kortikosteroide (ICS); eosinophile Granulozyten